Гидродинамика потока водоугольной суспензии на ситовой поверхности - Полулях, А.Д.; Сансиев, В.Г. (Геотехнічна механіка, 2005)
З застосуванням методу малого параметру одержано рішення рівнянь Нав’є-Стокса для течії водовугільної суспензії по ситовій поверхні з урахуванням змін в’язкості суспензії уздовж напряму руху. With application of a method of small parameter the solution of the equations of the NavierStokes for fluxion watercoal suspension on a screen surface is obtained in view of change of viscosity of suspension along a direction of driving.